Endoscopic bile duct stenting for common hepatic duct iatrogenic E2 class injury following non-planned laparoscopic cholecystectomy: case report - Grigaliūnas, Aurelijus; Lunevičius, Raimundas; Kuliešius, Žygimantas; Praleikienė, Lina (Lietuvos chirurgija, 2015)
Background Open reconstructive bile duct surgery is a standard procedure for Bismuth–Strasberg E class iatrogenic injury of common hepatic or common bile duct. We aimed to describe an endoscopic stenting of the extra-hepatic bile duct due to Bismuth– Strasberg E2 class iatrogenic injury of common hepatic duct related to emergency laparoscopic cholecystectomy for acute prolonged perforated calculus cholecystitis and subhepatic abscess. Case report The E2 class injury to the common hepatic duct detected via ERCP and fistula cholangiography for an 81 year-old-male patient following ‘difficult’ emergency laparoscopic cholecystectomy and drainage of the subhepatic space. A plastic biliary stent inserted during the ERCP procedure for the temporary management of a high-volume bile leak from the common hepatic duct. When a 1 cm long stricture was diagnosed three months after the original gallbladder surgery (Fig. 4), Hanarostent BCT-10-080-180 was inserted to cure the patient. The patient is well and without symptoms of cholangitis within six months following the final biliary stenting. Conclusions Endoscopic biliary stenting is an alternative management option for E2 (and, potentially, for E1) class injury of the common hepatic duct in patients with a limited physiological reserve. The case shows that a step-wise approach to 25 principles to minimize the risk to patients undergoing laparoscopic cholecystectomy (Lithuanian Surgery 2015, 14: 14–27) should be a requirement in all institutions admitting patients with a biliary disease.